Pengaruh Gaya Hidup, Pendapatan, dan Religiusitas Terhadap Keputusan Pembelian Di Toko Ama Griya Hijab Sidayu - Albar, Kholid (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2023)
The world fashion industry is currently experiencing rapid development where this industry is being played by companies that are engaged in the world of fashion ranging from fashion companies on a local scale to well-known brand fashion companies. In Indonesia itself, the fashion industry can be said to be quite interesting, this is because many of the Muslim women who become designers, so that producers and consumers in the fashion industry are many of the Muslim women who then they plunge and start this business while carrying out da'wah activities related to the style and dress patterns of a good Muslimah. As the world of fashion develops, women can still look elegant and attractive without having to violate the provisions of shara' which is a requirement as a Muslimah. This study aims to determine the effect of income, lifestyle and religiosity variables simultaneously or partially on purchasing decisions at the ama griya hijab sidayu gresik boutique. This study aims to determine what factors are most dominant in influencing purchasing decisions from income, lifestyle and religiosity variables. Respondents totaled 100 people. Data collection was carried out using a questionnaire instrument. The data analysis technique used is multiple linear regression analysis. The conclusion of this study is that together the independent variables have a positive and significant effect on purchasing decisions.